The Impact of a Dedicated “Hot List” on the In-Patient Management of Patients With Acute Gallstone-Related Disease - Jamdar, Saurabh; Chandrabalan, Vishnu V.; Obeidallah, Rami; Stathakis, Panagiotis; Siriwardena, Ajith K.; Sheen, Aali J. (Frontiers in Surgery, 2021)
Background Index admission laparoscopic cholecystectomy is the standard of care for patients admitted to hospital with symptomatic acute cholecystitis. The same standard applies to patients suffering with mild acute biliary pancreatitis. Operating theatre capacity can be a significant constraint to same admission surgery. This study assesses the impact of dedicated theatre capacity provided by a specialist surgical team on rates of index admission cholecystectomy Methods This clinical cohort study compares the management of patients with symptomatic gallstone disease admitted to a tertiary care university teaching hospital over two equal but chronologically separate time periods. The periods were before and after service reconfiguration including a specialist HPB service with dedicated operating theatre time allocation. Results There was a significant difference in the number of admissions over the two time periods with a greater proportion of patients having index admission surgery in the second time period with correspondingly fewer having more than one admission during this latter time period. In the second time period, 43% of patients underwent index admission cholecystectomy compared to 23% in the first (P<0.001). The duration of surgery was shorter for patients undergoing surgery during the second time period (135 [102 – 178] minutes in the first period and in the second period 106 [89 -145] minutes) (P=0.02). Discussion This paper shows that the concentration of theatre resources and surgical expertise into regular theatre access for patients undergoing urgent laparoscopic cholecystectomy is an effective and safe model for dealing with acute biliary disease.